Internal Bone Architecture in the Zygoma of Human and Pan. Issue 12 (15th November 2016) - Pryor McIntosh, Leslie; Strait, David S.; Ledogar, Justin A.; Smith, Amanda L.; Ross, Callum F.; Wang, Qian; Opperman, Lynne A.; Dechow, Paul C.
ABSTRACT: The internal and external anatomy of the primate zygoma is central to orofacial function, health, and disease. The importance of variation in its gross morphology across extinct and extant primate forms has been established using finite element analysis, but its internal structure has yet to be explored. In this study, µCT is used to characterize trabecular bone morphometry in two separate regions of the zygoma of humans and Pan . Trabecular anisotropy and orientation are compared with strain orientations observed in trabecular regions of finite element models of four Pan crania. The results of this study show that trabecular bone morphometry, anisotropy, and orientation are highly compatible with strain orientation and magnitude in the finite element models. Trabecular bone in the zygoma is largely orthotropic (with bone orientation differing in three mutually orthogonal directions), with its primary orientation lying in the mediolateral direction. Trabecular bone in the zygomatic region appears to be highly influenced by the local strain environment, and thus may be closely linked to orofacial function. Anat Rec, 299:1704–1717, 2016. © 2016 Wiley Periodicals, Inc.